Analisis Suasana Toko, Potongan Harga Dan Penataan Produk Terhadap Pembelian Impulsif - Safitri, Nadia; Hadi, Prasetyo; Dwi, Bernadin (Jurnal Ilmiah Manajemen Kesatuan, 2020)
This research is a quantitative study that aims to determine the effect of the atmosphere of the store, price discounts and product arrangement on impulsive purchases. The population in this study are consumers who have shopped at the Ramayana Department Store in the Jakarta area. Sample size was taken as many as 75 respondents, with non-probability sampling methods especially purposive sampling. Data collection in this study was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method with SmartPLS software version 3.0. The results of this study indicate that (1) store atmosphere does not affect impulsive purchases with a path coefficient of 0.067. (2) the price discount significantly influences impulsive purchases with a path coefficient of 0.417. (3) product structuring significantly influences impulsive purchases with a path coefficient of 0.482. Keywords: Store Atmosphere, Price Discount, Display Product, Impulse Buying